Perbedaan Tingkat Keragaman Pangan Balita dan Tingkat Pendidikan Orang Tua di Rumah Tangga Kawasan Rumah Pangan Lestari (KRPL) Dan Non KRPL - Annisa Fidya Lestari; Ratna Setyaningsih (Amerta Nutrition, 2018)
Background: Sustainable Reserve Food Garden Area (KRPL) is program that to increase family dietary diversity, such as children. Children’s dietary diversity can affect to nutritional adequacy and can impact to growth process. The factor that can affect successful of KRPL program is parents’ education level.Objectives: The purpose of this study was to identify the difference between children’s dietary diversity level, household income level, and parents’ education level in sustainable reserve food garden area (KRPL) and non KRPL household in Kamal sub-district, Bangkalan district, Madura.  Method: This was an observational study with case control comparative study design was conducted among 25 children in KRPL area and 25 children in non KRPL area with mother or other family member as respondents. Simple random sampling method was used to select the samples. Children and parents’ characteristic were asked to answer structured questionnaire. Children dietary diversity level was asked by Individual Dietary Diversity Score (IDDS) instrument. The data was analyzed with Mann Whitney statistic test. Result: Children that involved in this study, either in KRPL or non KRPL area, was less than the same 35 months old (52%). Children from KRPL area was mostly girls (64%), while children from non KPRL area was mostly boys (56%). Children dietary diversity condition in KRPL area was low (52%), while children dietary diversity level in non KRPL area was sufficient (64%). Children who lived in KRPL area not always have diverse intake. The result showed that there was no difference between children dietary diversity level in KRPL and non KRPL area (p=0.259). Household income level on KRPL area was higher (68%) if compared to household on non KRPL area (44%). Parents’ education level in KRPL area was classified high (father=88%, mother=88%), while that parents’ education level in non KRPL area classified low (father=88%, mother=100%) (p=0.000). Parents in KRPL area have higher education level compare to parents in non KPRL area. Conclusion: Children dietary diversity in KRPL area are not different with non KRPL area. Children who lived in KRPL area not always have diverse intake. There is difference between household’s income level and parents’ education level. Household in KRPL area have higher income and parents in KRPL area have higher education level compare to households and parents in non KPRL area. ABSTRAKLatar Belakang: Kawasan Rumah Pangan Lestari (KRPL) merupakan program yang bertujuan untuk memperbaiki dan meningkatkan keragaman pangan keluarga, salah satunya balita. Keragaman pangan pada balita dapat berpengaruh pada kecukupan kebutuhan gizi dan berdampak pada proses pertumbuhannya. Salah satu faktor yang dapat mempengaruhi keberhasilan program KPRL adalah tingkat pendidikan orang tua.Tujuan: Tujuan dari penelitian ini adalah untuk mengidentifikasi perbedaan tingkat keragaman pangan balita dan tingkat pendapatan keluarga, dan tingkat pendidikan orang tua di rumah tangga Kawasan Rumah Pangan Lestari (KRPL) dan non KRPL Kecamatan Kamal, Kabupaten Bangkalan, Madura.Metode: Penelitian observasional dengan rancang bangun penelitian potong lintang komparatif dilakukan pada subjek penelitian yang terdiri dari 25 balita di wilayah KRPL dan 25 balita di wilayah non KRPL dengan ibu atau anggota keluarga lainnya sebagai responden. Metode simple random sampling digunakan untuk memilih sampel. Karakteristik balita dan orang tua ditanyakan melalui kuesioner. Tingkat keragaman pangan balita ditanyakan melalui instrumen Individual Dietary Diversity Score (IDDS) Data dianalisis menggunakan uji statistik Mann Whitney.Hasil: Balita yang terlibat dalam penelitian ini, baik di area KPRL maupun non KPRL, sebagian besar berusia kurang dari sama dengan 35 bulan (52%). Balita yang berasal dari wilayah KRPL sebagian besar perempuan (64%), sedangkan dari wilayah non KPRL sebagian besar laki-laki (56%). Kondisi tingkat keragaman pangan balita di wilayah KRPL tergolong rendah (52%), sedangkan tingkat keragaman pangan balita di wilayah non KRPL tergolong cukup (64%). Balita yang tinggal di rumah tangga KRPL tidak selalu mengonsumsi makanan yang beragam. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan tingkat keragaman pangan balita di wilayah KRPL dan non KPRL (p=0,259). Tingkat pendapatan keluarga balita di wilayah KRPL lebih tinggi (68%) apabila dibandingkan dengan wilayah non KPRL (44%). Tingkat pendidikan orang tua di wilayah KRPL tergolong tinggi (ayah=88%, ibu=88%), sedangkan tingkat pendidikan orang tua di wilayah non KRPL tergolong rendah (ayah=88%, ibu=100%) (p=0,000).Kesimpulan: Tingkat keragaman pangan balita di area KRPL tidak berbeda dengan balita di area non KPRL. Terdapat perbedaan tingkat pendapatan keluarga dan tingkat pendidikan orang tua balita. Keluarga di wilayah KRPL memiliki tingkat pendapatan yang lebih tinggi dan orang tua di area KRPL memiliki tingkat pendidikan lebih tinggi apabila dibandingkan dengan rumah tangga dan orang tua di wilayah non KPRL.